Evaluation of the tropical humid forest through fractional cover analysis and GIS techniques at Yuracyacu river watershed, peruvian's Amazon - Gómez-Lora, Jhon Walter; Gallo-Ramos, Víctor Hugo; Camacho-Zorogastúa, Katherine del Carmen (Instituto de Ecología, A.C., 2021)
This paper evaluated the tropical humid forest at Yuracyacu watershed during the period 1989-2010. For this, 6 Landsat satellite images were used from the Thematic Mapper sensor for the years 1989, 1995, 2001, 2006, 2008, 2010, which the respective processing was carried out using CLASlite by analyzing the fractional cover. During the period 1989-1995 a loss of 18.2 km2 of the forest cover was obtained, for the period 1995-2001 the forest cover was recovered in a ratio of 1.2 km2/year; for the periods 2001-2006, 2006-2008, and 2008-2010 it was pbserved the progressive decline of the tropical rain forest, these losses being 8.9 km2, 3.4 km2 and 7.5 km2 respectively. In the 21 years, 32 km2 of Amazon rainforest have been lost from the sub-basin with a deforestation rate -1.2% per year, the highest rate of deforestation was found in the period 1989-1995, which is -2.27%. The model for determining future tropical forest scenarios in the watershed estimated a resulting area of 89.1 km2 by 2030, demonstrating the progressive decrease of tropical humid forest. Finally, in the validation of the results, a global reliability of 85% and a Kappa index of 0.65 were obtained indicating the goodness and precision of the classification. The results of this study will guide actions for the conservation and management of the tropical rainforest of the watershed.